IS IT POSSIBLE TO GENERATE SOCIAL CAPITAL WITH GOVERNMENT ACTIONS? THE PUBLIC SPACES RESCUE PROGRAM AND CITIZEN PARTICIPATION IN WESTERN MEXICO - Ángel Lara , Hirám Abel; Martínez Gallegos , Karen (Journal of Public Governance and Policy: Latin American Review, 2015)
This paper analyzes the Public Spaces Rescue Program -Programa de Rescatede Espacios Públicos- (PREP) as part of the federal government’s strategyto generate or consolidate social capital within communities, areas orneighborhoods affected by problems related to violence and criminality, particularlyin the municipality of Zapopan, Jalisco from 2007 to 2012.First, the experience exposes that social capital is not a resource thatcan be generated by government intervention because it can existor not prior to it. Second, social capital itself, is not a resource thateradicates violence and crime conditions in a determined social andgeographical space and third, social capital depends as well on thegroup’s interest to organize around a specific goal.From the perspective of Durston (2001), trust, reciprocity and cooperationare infrequent social assets that are hard to maintain over timeand require constant interaction.